Biomechanical Strength of Scaphoid Partial Unions - Brekke, Adam C.; Snoddy, Mark C.; Lee, Donald H.; Richard, Marc J.; Desai, Mihir J. (Journal of Wrist Surgery, 2018)
Background It remains unknown how much force a partially united scaphoid can sustain without refracturing. This is critical in determining when to discontinue immobilization in active individuals.Purpose The purpose of this study was to test the biomechanical strength of simulated partially united scaphoids. We hypothesized that no difference would exist in load-to-failure or failure mechanism in scaphoids with 50% or more bone at the waist versus intact scaphoids.Materials and Methods Forty-one cadaver scaphoids were divided into four groups, three experimental osteotomy groups (25, 50, and 75% of the scaphoid waist) and one control group. Each was subjected to a physiologic cantilever force of 80 to 120 N for 4,000 cycles, followed by load to failure. Permanent deformation during physiologic testing and stiffness, max force, work-to-failure, and failure mechanism during load to failure were recorded.Results All scaphoids survived subfailure conditioning with no significant difference in permanent deformation. Intact scaphoids endured an average maximum load to failure of 334 versus 321, 297, and 342 N for 25, 50, and 75% groups, respectively, with no significant variance. There were no significant differences in stiffness or work to failure between intact, 25, 50, and 75% groups. One specimen from each osteotomy group failed by fracturing through the osteotomy; all others failed near the distal pole loading site.Conclusion All groups behaved similarly under physiologic and load-to-failure testing, suggesting that inherent stability is maintained with at least 25% of the scaphoid waist intact.Clinical Relevance The data provide valuable information regarding partial scaphoid union and supports mobilization once 25% union is achieved.
Keywords: scaphoid fracture; scaphoid union; biomechanical strength